Efficacy and safety of a universal influenza A vaccine (MVA-NP+M1) in adults when given after seasonal quadrivalent influenza vaccine immunisation (FLU009): a phase 2b, randomised, double-blind trial. Issue 6 (June 2022) - Evans, Thomas G; Bussey, Louise; Eagling-Vose, Elizabeth; Rutkowski, Kathryn; Ellis, Chris; Argent, Chris; Griffin, Paul; Kim, Joshua; Thackwray, Susan; Shakib, Sepehr; Doughty, Julia; Gillies, John; et al.
Summary: Background: In animal, epidemiological, and human challenge studies, a pre-existing T-cell response to internal proteins of influenza A has been associated with improved virological and disease outcomes. The aim of this study was to assess whether inducing additional responses to conserved CD4 and CD8 T-cell antigens provides added benefit to standard influenza vaccination. Methods: We designed a phase 2b, randomised, placebo-controlled, double-blind trial of a recombinant viral-vectored vaccine (modified vaccinia Ankara expressing virus nucleoprotein and matrix protein 1; MVA-NP+M1), which has been shown to induce both CD4 and CD8 T cells, at eight outpatient clinical trial sites in Australia over two consecutive influenza seasons. We recruited non-immunosuppressed adults (≥18 years) who had received the 2019 quadrivalent influenza vaccine (QIV) vaccine within 28 days before study enrolment and randomisation (day 0). Participants were randomly assigned (1:1) according to a computer-generated random sequence to receive one dose of 1·5 × 10 8 plaque-forming units of MVA-NP+M1 or saline (placebo) intramuscularly. Randomisation was stratified by age (<65 years or ≥65 years). The patients and trial assessors were masked to treatment assignment. During the subsequent influenza seasons, participants with symptoms related to respiratory illness or influenza-like illness were to attend the clinic within 72 h of symptom onset for two nasal swabs for influenza testing by quantitative RT-PCR. The primary endpoint was the incidence rate of laboratory-confirmed influenza in the intention-to-treat (ITT) population. Safety (solicited adverse events within 7 days and unsolicited adverse events within 28 days after study vaccination, and serious adverse events for the study duration) was assessed in all randomly assigned participants who received at least one vaccination (according to the treatment received). The trial is registered with ClinicalTrials.gov, NCT03880474 . Findings: Between April 2 and June 14, 2019, 2152 adults were randomly allocated and received MVA-NP+M1 (n=1077) or placebo (n=1075), comprising the efficacy (ITT) analysis set. Participants were followed up throughout the 2019 Australia influenza season (May 1 to Oct 15, 2019). 419 (19·5%) of 2152 participants were aged 65 years or older. The incidence of laboratory-confirmed influenza did not differ between the MVA-NP+M1 group (35 of 1077 participants; 3·25% [95% CI 2·31–4·44]) and the placebo group (23 of 1075; 2·14% [1·39–3·14]; Fisher's exact p=0·14). 23 severe solicited local injection site reactions were reported in 13 (0·6%) of 2152 participants, 22 of which were reported in the MVA-NP + M1 group (in 12 [1·1%] participants). 100 severe systemic events were reported in 45 (4·2%) MVA-NP + M1 recipients, and 20 were reported in 14 (1·3%) placebo recipients. Three unsolicited grade 3 events in three participants (two headache and one nausea, all in the MVA-NP+M1 group) were deemed vaccine related. 21 serious adverse events were reported in 18 (1·7%) of 1077 participants in the MVA-NP+M1 group and 25 serious adverse events were reported in 22 (2·0%) of 1075 participants in the placebo group; none were considered vaccine related. The trial was stopped after one season for futility on the recommendation of the data monitoring committee. Interpretation: MVA-NP+M1 was well tolerated with no vaccine-associated serious adverse events. A vaccine designed to induce moderate T-cell responses to the cross-reactive internal proteins of influenza A did not lead to improved incidence when given within 28 days after standard QIV immunisation. A greater magnitude of T-cell response with a different vaccine or regimen, or localisation in the lungs via alternative delivery, such as intranasal or aerosol, might be successful and require further investigation. Funding: Vaccitech.